Perception of Health Workers on Preventing COVID-19 Transmission Behavior based on Work Area and Exposure - Rio Dananjaya; Rudi Wisaksana; Primal Sudjana; Shelly Iskandar (Universitas Islam Bandung, 2022)
Coronavirus disease 2019 (COVID-19) emerged at the end of 2019 and spread worldwide, becoming a pandemic on March 11, 2020. Agents, hosts, and the environment influence disease transmission. Perception influences healthy behavior in preventing disease transmission. This study aims to determine differences in the perception of health care workers (HCWs) on COVID-19 prevention behavior based on the area of work and exposure. This study is a cross-sectional study with a survey method using the health belief model questionnaire with research subjects who were HCWs on duty during the COVID-19 pandemic from May to July 2021 in Dr. Hasan Sadikin General Hospital. Statistical tests used were chi-square and Kruskal-Walis tests. From 346 subjects, it was found that the perception of susceptibility and self-efficacy of HCW in the yellow and red zones was higher than in the green zone (p=0.002). In comparison, the perception of barriers in the yellow zone was higher than in the red area (p=0.014). Health care workers had relatively similar mean scores in terms of knowledge (median 7 of 9), perceived benefits (median 27 of 30), cues to action (median 20 of 20), and perceived severity (median 19 of 30). Based on the history of exposure, the parameter of cues to the action of HCWs exposed to COVID-19 was better than those never exposed (p=0.009). HCW of Dr. Hasan Sadikin General Hospital has good knowledge and perception of the prevention of COVID-19. Differences in the perception of HCW between the work area and exposure history require more targeted and specific educational interventions and actions.